Organizational Effectiveness Related to Disaster Risk Reduction Management in Taytay, Rizal, Philippines: Perspective from the Academic Leaders - Lao, Clarice; San Pedro, Jay R; Caballes, Dennis (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
Prior to the global health crisis, Taytay, Rizal, Philippines is vulnerable to the different natural disasters and calamities. With this, the researchers see the value of investigating disaster risk reduction management being practiced by the local government unit through the lens of academic leaders. With this, a descriptive research design was implored to gather and substantiate the organizational effectiveness with the research niche. The 100 respondents were selected through purposive and snow-ball sampling who academic leaders from the various educational institutions within the municipality of Taytay, Rizal, Philippines. Based on the findings, it shows that the local government unit of Taytay, Rizal has manifested an effective organizational approach in the implementation of the disaster risk reduction management as perceived by the academic leaders. Afterward, the researchers draft an action plan to further strengthen the disaster risk reduction management plan of the local government unit.